Factor Structure and Measurement Invariance for the Cognitive Emotion Regulation Questionnaire (CERQ) Among Women Newly Diagnosed With Breast Cancer - Li, Lingyan; Li, Shichen; Wang, Yuping; Yang, Yanjie; Zhu, Xiongzhao (Frontiers in Psychology, 2019)
Background: Given that emotion regulation counts for much in breast cancer, it is important to well understand its construct. The Cognitive Emotion Regulation questionnaire (CERQ) is a widely applied instrument for measuring conscious cognitive coping strategies in both general and clinical sample; however, there are no data on its factor structure in women with breast cancer, not to mention evidence of measurement invariance (MI) across sociodemographic variables. Thus, the purpose of the present study was to examine the latent factor structure and MI between different sociodemographic groups for CERQ in the specific patients. Method: The sample consists of 1032 women newly diagnosed with breast cancer, with a mean age of 47.54 years (SD = 8.51). The latent factor structure for CERQ was tested using Confirmatory Factor Analysis (CFA). Further, MI various sociodemographic variables was evaluated by a series of multiple-group CFA process. Results: The nine-factor CFA model well fitted the data collected in women with breast cancer. Also this nine-factor structure had strong factorial invariance across age, residence place, education levels and employment status. Conclusion: This study firstly examined the latent factor structure for CERQ among Chinese women with malignancy and measurement invariance across various sociodemographic variables, which deepens understanding of the construct for CERQ as a useful tool for assessing patients’ conscious cognitive component of emotion regulation based on self-report.